2009
DOI: 10.1136/bcr.06.2008.0284
|View full text |Cite
|
Sign up to set email alerts
|

Variability and diversity of the electrical cardiac systole

Abstract: The electrical cardiac systole originates from the beginning of the P wave (atrial depolarisation) until the end of the downward branch of the T wave (ventricular repolarisation). It includes, therefore, succession P-QRS-T and its corresponding intervals and segments: PQ, ST, and QT. The mathematical possibilities of variability in the length of the electrical systole of the heart may be diverse. It is well documented and established that such changes in length may make the myocardial cells more vulnerable and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…We have demonstrated the presence of this pattern in several persons with symptoms of childhood convulsions -diagnosed as epilepsy despite not display any epileptic focus on studies of electroencephalography (EEF) -as well as nocturnal tachycardia crisis and syncope events related to repetitive physical effort [8][9][10]. For some authors, the electrical cardiac systole comprises only the QT interval (ventricular cycle) [11], but we think that the depolarization atrial must be included [1,2,10] Electrical cardiac systole comprises…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have demonstrated the presence of this pattern in several persons with symptoms of childhood convulsions -diagnosed as epilepsy despite not display any epileptic focus on studies of electroencephalography (EEF) -as well as nocturnal tachycardia crisis and syncope events related to repetitive physical effort [8][9][10]. For some authors, the electrical cardiac systole comprises only the QT interval (ventricular cycle) [11], but we think that the depolarization atrial must be included [1,2,10] Electrical cardiac systole comprises…”
Section: Discussionmentioning
confidence: 99%
“…For some authors, the electrical cardiac systole comprises only the QT interval (ventricular cycle) [11], but we think that the depolarization atrial must be included [1,2,10] Electrical cardiac systole comprises…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Half of the patients also had atrial fibrillation inducibility. The ventricular effective refractory period was set at values below 150 msec, and the infusion of flecainide and other drugs of I-class determine a prolongation between 30 and 100 msec [40,41].…”
Section: Electrophysiological Studymentioning
confidence: 99%
“…Thus, for example, Breijo-Marquez et al have found this "Breijo Pattern" associated with a "Wellens syndrome "(also know as Wellens pattern) [2]. Breijo-Márquez et al have also published a case with the presence of a Wolff -Parkinson-White pattern associated with a long QT interval in an intermittent way [3].…”
mentioning
confidence: 99%